Effectiveness of Extract of Jeringau Rhizome (Acoruscalamus L.) on Mushrooms Sclerotium rolfsii Sacc. Causing Stem Rot on Peanut Plant (Arachis hypogaea L.) - Ni Luh Gede Ambaradewi (Journal of Sustainable Development Science, 2019)
Sclerotium rolfsii Sacc. is one of the important pathogens in peanuts. The controls that have been undertaken by farmers generally use synthetic pesticides. However, the use of synthetic pesticides has various negative impacts on the environment and human health. Therefore a technology is needed to produce environmentally friendly pesticides and effectively control stem rot. This study aims to determine the effectiveness of the Jeringau rhizome extract against S. Rolfsii fungi. The results showed that the crude extract of the Jeringau rhizome was able to inhibit the growth of S. rolfsii fungi in vitro on PDA media. Minimum Inhibitory Concentration (MIC) crude extract of jeringau rhizome was 0.50%. The inhibitory power of the extract with a concentration of 0.10% to 0.50% increased from 48.17% to 100%. The treatment of extract concentration of 0.50% showed fungicidal properties against S. rolfsii.